Kaposi Varicelliform Eruption Complicated by Steroids: A Case Report and Review of Literature - Goswami, Aniket; Verma, Shikha; Bikash, Chingshubam; Kalita, Pranjal (Acta medica Lituanica, 2025)
Kaposi varicelliform eruption (KVE) is a severe disseminated cutaneous infection mainly caused by herpes simplex virus (HSV-1 or HSV-2). Herein, we report a case of KVE which was misdiagnosed elsewhere as a case of toxic epidermal necrolysis and received systemic steroids, following which, the patient’s condition deteriorated. After being diagnosed as a case of KVE with the aid of tzanck smear, the patient was initiated on acyclovir and responded dramatically to the treatment. This case underscores the critical value of simple bedside tests, such as the tzanck smear, for rapid diagnosis of KVE and the timely initiation of treatment, facilitating prompt recovery. Additionally, it highlights the importance of histopathological evaluation in ambiguous cases so that to prevent mismanagement and ensure accurate diagnosis and the appropriate care.
Keywords: kaposi varicelliform eruption; acyclovir; tzanck smear; steroid; eczema herpeticum